Higher educational building defects in Perak / Muhammad Syafiq Muhd Rozi and Noraini Md Zain - Muhd Rozi, Muhammad Syafiq; Md Zain, Noraini (2019)
Education buildings are prone to building defects and their care is very important to make sure the building is safe to use and maintained. Defects in educational buildings are hazardous to users especially students. For example, education building at Beaufort, Sabah which has defect in the wall structure causing the wall of the building to collapse. Furthermore, this study is about to improve the defect management of the higher educational building in Perak. The objectives of this study is to know the types of defects, the causes of the defects, and to investigates method to overcome the defect in higher educational building. This study uses observation and questionnaires to collect data from the respondents. For objective 1, the result from observation show the common defects found are cracks, dampness, flaking paintwork and plaster, fungus attacks are the most occurring type of defect in educational buildings in Perak. For objective 2 and objective 3, the questionnaires were distributed to 92 targeted respondents which are the maintenance team. In addition, the SPSS version 25 was utilized in analyzing the collected data. Amongst the main reasons that causes defects are age of the building itself. The famous method to overcame the defect is replacing and install new material to recover the defect.